Gen Z Mindset in the Era of Rapid Advances in Science and Technology and Physics - Wicaksono, Haikal Oke; Wulansari, Rania; Ash-Shaba, Qanita Hukma; Ernasari, Ernasari; Mahardika, I Ketut; handono, Sri (International Journal of Education, Information Technology, and Others, 2023)
Humans are God's most perfect creatures compared to other creatures, because humans are given reason to think. However, not all humans have this level of intelligence or sensitivity in logical, critical, creative or innovative thinking. This is based on the development of human thought patterns that are not simultaneous. Human thought patterns are influenced by the surrounding circumstances and of course influenced by the human will itself. If you look back, in the Babylonian era, ancient humans (approximately 650 BC) only had the mindset of maintaining their survival by moving around (nomadic). This is because at that time human were still based on customs and still believed in myths. This is different from today where humans have developed more in terms of thought patterns. Human today tend to have a higher level of curiosity, especially with the current advances in science and technology. . Science and technology develop together with science, so that the two have a continuous relationship. So human thought patterns are greatly influenced by knowledge which is becoming increasingly widespread along with advances in science and technology